2017
DOI: 10.1021/acsnano.7b02322
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Metal Electrode for Organic–Inorganic Hybrid Nanowire Solar Cells

Abstract: We demonstrate here an embedded metal electrode for highly efficient organic-inorganic hybrid nanowire solar cells. The electrode proposed here is an effective alternative to the conventional bus and finger electrode which leads to a localized short circuit at a direct Si/metal contact and has a poor collection efficiency due to a nonoptimized electrode design. In our design, a Ag/SiO electrode is embedded into a Si substrate while being positioned between Si nanowire arrays underneath poly(3,4-ethylenedioxyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 36 publications
0
40
0
4
Order By: Relevance
“…Transparent conducting electrodes have drawn great attention in many optoelectronics applications, such as solar cells, flat panel displays, and touch panels . Indium tin oxide (ITO) films have been the most dominant transparent conducting electrodes due to their high transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent conducting electrodes have drawn great attention in many optoelectronics applications, such as solar cells, flat panel displays, and touch panels . Indium tin oxide (ITO) films have been the most dominant transparent conducting electrodes due to their high transparency.…”
Section: Introductionmentioning
confidence: 99%
“…This insertion layer also enhanced the V oc from 0.52 to 0.54 V, and an FF from 66.4 to 69.5%. Um et al fabricated Si NW/PEDOT:PSS solar cells [164]. In their design, a Ag/SiO 2 electrode was embedded into the Si substrate and positioned between Si NW arrays underneath PEDOT:PSS, which can facilitate suppressing recombinations at the Si-Ag interface and notably improve the fabrication reproducibility.…”
Section: Design For Novel High-efficiency and Low-cost Solar Cellsmentioning
confidence: 99%
“…This solar cell had an efficiency of 11.48%, which was higher than the planar solar cells (6.16~7.59%) and the micropyramid solar cells without NWs (10.37~10.96%). At present, the polymer/NW hybrid solar cell has reached an efficiency of well over 10% [164,166]. However, these high-efficiency hybrid solar cells were using top-down etched NWs [167,168].…”
Section: Design For Novel High-efficiency and Low-cost Solar Cellsmentioning
confidence: 99%
“…[16][17][18][19] Recently it has been reported that efficiencies as high as 16% can be obtained for Si nanowires/PEDOT: PSS hybrid heterojunction solar cells using embedded metal micro grid electrode. [20] Other reports mention using different materials like DMSO, IPA, SDS mixed in various conditions (for example molecular weights and ratios, temperature, sonication, stirring, etc.) with PEDOT:PSS to increase the conductivity of the PEDOT:PSS layer.…”
Section: Introductionmentioning
confidence: 99%